Wound Healing Potency of Edible Bird’s Nest - Alysia, Jessica; Stella, Maureen Miracle; Widjaja, Maureen; Wijaya, Lorettha (Indonesian Journal of Global Health Research, 2025)
Edible bird's nest (EBN) or swiftlet's nest has recently been used extensively in regenerative medicine. This study aims to give a more thorough overview on the efficacy of EBN as a wound-healing agent. Method: We searched literature through several databases: Google Scholar, PubMed, Proquest, JSTOR, EBSCOhost, and SAGE. The keywords used were "bird nest, scar, wound healing" and their synonyms. The inclusion criteria were original articles written in English and assessed the effects of EBN in the wound healing process. We found 9 in vitro studies and 4 in vivo studies reporting wound healing effect of EBN, both macroscopically and microscopically. EBN could increase wound healing process through several mechanisms, such as cell proliferation, anti-oxidants, anti-inflammation, increased collagen synthesis, and tissue hydration. EBN has the potential to be used as a natural bioactive agent to increase the wound healing process.